2016
DOI: 10.1007/s12282-016-0683-6
|View full text |Cite
|
Sign up to set email alerts
|

Prolyl hydroxylase mediated inhibition of fatty acid synthase to combat tumor growth in mammary gland carcinoma

Abstract: Cancer is a group of cells which grow in an uncontrolled manner and invades to the adjacent organs to form malignant tumors. Tumor hypoxia results due to contrast between the cellular oxygen expenditure and oxygen supply to the cells. Hypoxia inducible factor (HIF) is a heterodimeric transcription factor encompass of oxygen sensitive α subunit and constitutively expressed β subunit both of which are basic helix-loop-helix protein. The stability of HIF is primarily regulated by post translational prolyl hydroxy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 86 publications
1
15
0
Order By: Relevance
“…14 It was previously hypothesized that the chemical activation of PHD-2 can downregulate the overexpressed level of HIF-1a and fatty acid synthase (FASN) in tumor cells. 15,16 In fact, previous preliminary reports also suggested three activators of PHD-2, named KRH102053, KRH102140 and R59949, with anticancer potential. [17][18][19] In consideration of the above and in search of potential activators of PHD-2 with anticancer activity, we considered it worth screening structural analogs of PHD-2 and validating their anticancer efficacy through in vitro and in vivo studies.…”
Section: Introductionmentioning
confidence: 99%
“…14 It was previously hypothesized that the chemical activation of PHD-2 can downregulate the overexpressed level of HIF-1a and fatty acid synthase (FASN) in tumor cells. 15,16 In fact, previous preliminary reports also suggested three activators of PHD-2, named KRH102053, KRH102140 and R59949, with anticancer potential. [17][18][19] In consideration of the above and in search of potential activators of PHD-2 with anticancer activity, we considered it worth screening structural analogs of PHD-2 and validating their anticancer efficacy through in vitro and in vivo studies.…”
Section: Introductionmentioning
confidence: 99%
“…Hypoxia-inducible factor-1α (HIF-1α) is an intracellular key factor that mediates many cellular responses to hypoxia. Intensive studies have demonstrated that HIF-1α is a metabolic regulator which regulates the transcription of genes involved in aerobic glycolysis or fatty acid synthesis during cancer development and oncovirus infection ( Singh et al., 2016 ; Lo et al., 2017 ). It has been shown that KSHV targets and activates HIF-1α, and several KSHV-encoded genes are in turn activated by HIF-1α, suggesting HIF-1α might play a substantial role in KSHV-induced oncogenesis.…”
Section: Mechanisms By Which Kshv Controls Aerobic Glycolysis Glutaminolysis and Fatty Acid Synthesismentioning
confidence: 99%
“…Despite of much progress in the eld of cancer radiation and chemotherapy, treatment and management of mammary gland carcinoma is still very di cult [3]. Moreover, failure of radiation and chemotherapy due to hypoxia in case of solid tumor of mammary gland is another encountered problem [4], Plethora of studies have revealed that hypoxia inducible factor-1α (HIF-1α) is the main component which takes various decisions to attain more hostile environment for proper growth and development of tumor cells even in the scarcity of oxygen [5]. It enhances the expressions of various genes involved in the metabolism of glucose and fatty acid synthesis pathway [6].…”
Section: Introductionmentioning
confidence: 99%